E-Voting Online Berbasis Website (Current Research in Education: Conference Series Journal, 2022)
E-voting is a voting system that utilizes information technology. E-voting system is a system that aims to facilitate the general election (election), especially regional head elections (regional elections). With this e-voting can facilitate data validation a voter, besides saving in terms of logistical needs on a budget. Also, recapitulation of time efficient vote counts. In designing a method that can develop the project is needed, so that to be able to realize projects in web-based online Voting can use the waterfall method. This waterfall method, in a project among others: Requirement, design, implementation, integration and testing, operation and maintenance. The e-voting system is online, making it possible to access it anywhere as long it is connected to the internet network. The e-voting system was built to reduce weaknesses, including problems in the redundance elections system, which reduced the use of paper material. This system is designed and built simply to make it easier for users to operate.